ANALISIS WACANA KRITIS PADA BERITA ONLINE SOLOPOS.COM TENTANG PILKADA BOYOLALI EDISI 9 DESEMBER 2020 - Arina Mana Sikana (Jurnal Membaca Bahasa dan Sastra Indonesia, 2021)
This research is motivated by the discourse on the online mass media solopos.com to determine the existence of power and marginalize someone in the discourse. The purpose of this study is to describe the use of Leeuwen's inclusion theory on political news and to see the alignments of journalists in the 2020 Boyolali regional election in the news maasa online solopos.com edition 9 December 2020 with the news title Said-Irawan Claims to Win the Boyolali Regional Election 2020, Achieves 95.6% of the votes . Data collection was carried out in three stages, (1) reading and understanding discourse on the 9 December 2020 edition of Solopos.com online mass media political news with the aim of obtaining a clear understanding of the content of the discourse to be studied, (2) marking the parts of the discourse that are related to Leeuwen's inclusion theory, and (3) inventory sentences in discourse related to Leeuwen's inclusion theory by sorting and classifying data. Based on the research results, it can be concluded that the discovery of Leeuwen's inclusion theory in an online news entitled Said-Irawan Claims to Win the 2020 Boyolali Regional Election, Gaining 95.6% of the vote. The inclusion theory is defined by three theories from the seven existing theories, namely objectivity-abstraction, nomination-categorization, and nomination-identification. From Leeuwen's three inclusion theories, it was found that there were 15 sentences containing this theory. It can be concluded that in writing criminal news, journalists do not marginalize victims and do not side with actors.